2018
DOI: 10.1038/s41598-018-28369-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy defects and related genetic variations in renal cell carcinoma with eosinophilic cytoplasmic inclusions

Abstract: The relationship between autophagy and tumour is well studied, but tumour cell morphological changes associated with autophagy defects are rarely reported, especially in renal cell carcinoma (RCC). We collected 10 renal tumour samples with characteristic eosinophilic cytoplasmic inclusions (ECIs) and found that the ECIs were majorly composed of sequestosome 1/P62, neighbor of BRCA1 gene 1 (NBR1), PEX14, and CATALASE1 (CAT1). Further, transmission electron microscopy analysis revealed that ECIs were aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Among the patients with biallelic ATG7 variants, a 71‐year‐old patient has developed an acoustic neuroma—a benign brain tumour, but longitudinal studies in other patients will provide further insight into whether this is related to ATG7 deficiency. Elsewhere, ATG7 polymorphisms associated with protective or pro‐carcinogenic properties have been reported (Yu et al , 2018 ; Wang et al , 2019b ), and elevation of ATG7 expression is associated with some bladder and lung cancers (Sun et al , 2016 ; Zhu et al , 2017 ). Furthermore, ATG7 levels may also be of prognostic value in breast cancers patients (Desai et al , 2013 ).…”
Section: Atg7 In Human Diseasementioning
confidence: 99%
“…Among the patients with biallelic ATG7 variants, a 71‐year‐old patient has developed an acoustic neuroma—a benign brain tumour, but longitudinal studies in other patients will provide further insight into whether this is related to ATG7 deficiency. Elsewhere, ATG7 polymorphisms associated with protective or pro‐carcinogenic properties have been reported (Yu et al , 2018 ; Wang et al , 2019b ), and elevation of ATG7 expression is associated with some bladder and lung cancers (Sun et al , 2016 ; Zhu et al , 2017 ). Furthermore, ATG7 levels may also be of prognostic value in breast cancers patients (Desai et al , 2013 ).…”
Section: Atg7 In Human Diseasementioning
confidence: 99%
“…Importantly, low expression of ATGs that is related to the process of autophagy nucleation, predicts poor prognosis in RCC (X. D. Liu et al, 2015a ; Yu et al, 2018 ). Liu et al found that most ccRCCs harbor allelic loss and/or mutation of ATG7.…”
Section: Introductionmentioning
confidence: 99%
“…39 Alternatively, p62 expression negatively correlates with autophagy, such that its accumulation reflects decreasing autophagy and its degradation indicates activated autophagy. 40,41 We found that OA significantly increased TGF-β1, LC3-II, and p62 protein expression in hepatocytes, suggesting damage to the hepatocyte autophagy flux and that G-Rg2 treatment significantly inhibited these increases, indicating that it restored hepatocyte autophagy flux (Figure 5). G-Rg2 reversed the LPS-induced autophagy flux increase of in HSCs and inhibited HSC activation (Figure 6), consistent with the trend for CDAHFD-induced autophagy in mouse livers (Figure 4).…”
Section: ■ Discussionmentioning
confidence: 91%